Does risk management matter? Evidence from the U.S. agricultural industry - Cornaggia, Jess (Journal of Financial Economics, 2013)
This article constructs triple-difference tests around shifts in the supply of risk management instruments available to agricultural producers to reveal a positive relation between risk management and productivity. This relation is more robust when producers adopt instruments with payoffs linked to group performance and weaker when payoffs are linked to individual performance. Additionally, productivity is particularly high among risk-managing producers in counties containing high levels of bank deposits, a proxy for access to finance. Overall, this article illuminates the relation between hedging and real firm outcomes as well as the interaction between access to finance and firms' risk management choices.